A clinic-epidemiological study of organophosphorus poisoning in children in a tertiary care medical college hospital - Anees-ur-Rahman, Mohammed; Suresh, Karthik; Visweswaraiah, Kumar Gowripura; Subbaraya, Ananda Kumar Tumkur (International Journal of Contemporary Pediatrics, 2020)
Background: Acute organophosphorus (OP) pesticide poisoning is widespread and is the most common poisoning in many developing countries and varies in different geographic regions. Organophosphorus compounds are anti acetyl cholinesterase which exert their toxicity by interfering with the normal function of acetylcholine, an essential neurotransmitter throughout the autonomic and central nervous system. Methods: The present study was conducted in department of pediatrics Sri Siddhartha medical college, Tumkur. All children with OP poisoning admitted in the pediatric ward were included in the study. Unknown compound/tablet poisoning, which was contradictory to the diagnosis of OP compound were excluded. Results: Out of 5,274 cases which were admitted in pediatric ward, 15 children were diagnosed as OP poisoning. In the present study the incidence of OP poisoning was 2.84%. Out of 15 cases 3 cases were below 1 year of age, 2 cases were in the age group of 1-5 years, 5 cases were in the age group of 6-10 years and 5 cases were seen in above 11 years of age. Among 15 cases 13 (86.7%) cases were accidental poisoning and 2 (13.3%) cases were attempt to suicide. Out of 15 cases 4 (26.7%) cases were seen in monsoon, 4 (26.7%) cases were seen in winter and 7 (46.6%) in summer season. Out of 15 cases 14 (93.3%) cases improved with treatment and 1 (6.7%) case discharged against medical advice. Conclusions: Most cases of accidental poisoning are preventable by close watch on the toddlers and younger children who have a habit of tasting unknown things. Educate school children in all aspects of childhood poisoning.